2010
DOI: 10.1103/revmodphys.82.499
|View full text |Cite
|
Sign up to set email alerts
|

Failure processes in elastic fiber bundles

Abstract: The fiber bundle model describes a collection of elastic fibers under load. The fibers fail sucessively and for each failure, the load distribution among the surviving fibers changes. Even though very simple, this model captures the essentials of failure processes in a large number of materials and settings. We present here a review of the fiber bundle model with different load redistribution mechanisms from the point of view of statistics and statistical physics rather than materials science, with a focus on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
398
1
16

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 331 publications
(443 citation statements)
references
References 177 publications
(222 reference statements)
28
398
1
16
Order By: Relevance
“…For the classical FBM (as described above) with forcecontrolled load, democratic load sharing, and without healing mechanisms, other authors have reported the following results (see reviews, e.g., [3,25]): The avalanche size S (number of broken fibers) is power-law distributed P (S) ≈ S b with b = 5/2 for all avalanches. If just the avalanches near failure are considered, the avalanche size is still power-law distributed but has a lower exponent with b = 3/2.…”
Section: Theoretical Considerations Of Fbm Model With Healingmentioning
confidence: 93%
See 4 more Smart Citations
“…For the classical FBM (as described above) with forcecontrolled load, democratic load sharing, and without healing mechanisms, other authors have reported the following results (see reviews, e.g., [3,25]): The avalanche size S (number of broken fibers) is power-law distributed P (S) ≈ S b with b = 5/2 for all avalanches. If just the avalanches near failure are considered, the avalanche size is still power-law distributed but has a lower exponent with b = 3/2.…”
Section: Theoretical Considerations Of Fbm Model With Healingmentioning
confidence: 93%
“…Moreover, it has been shown that the b value does not depend on the type of fiber strength distribution [27]. For these reasons the change of the b value towards failure is considered to be a good precursor, and the divergence of the order parameter and fiber failure rate can be used to predict the time when the bundle fails (e.g., [3]). Potentially damaging bursts or avalanches can be measured from outside without influencing the failure process (e.g., by acoustic emissions) and therefore the FBM theoretical results can be applied in practice.…”
Section: Consequences For Failure Predictionmentioning
confidence: 99%
See 3 more Smart Citations